Developing leadership capacity for Water−Energy−Food− Ecosystems (WEFE) nexus actors: Training manual - Governance Lab; Great International (2024)
This manual walks users through a programmatic process to develop the capacities of water-energy-food-ecosystems (WEFE) nexus actors, with an emphasis on women professionals. The program is designed to support diverse participants in navigating the complexities of managing the WEFE nexus in an integrated and equitable way to drive sustainable development efforts around the world. This manual describes the program structure and contents, along with clear guidance and practical facilitation strategies to enhance WEFE nexus knowledge and practices. While the program was developed in Nepal, the manual and the program it describes are intended for an international audience. As such, this program can serve as a flexible resource adaptable for a broad range of settings.